KINETIC STUDY OF THE REDUCTION OF FERRIC- 1, 10-ORTHOPHENAN- THROLINE WITH URANIUM (IV) DCTA - Perveen, R.; Naqvi, I. I. (The Nucleus, 2020)
The kinetics and mechanism of the reduction of ferric 1,10 orthophenanthroline by uranium (IV) trans â€“ 1,2 â€“ cyclohexanediaminetetraacetate was investigated in aqueous hydrochloric acid at 300C, at ionic strength 0.01-mole dm-3and pH 3.5. Rate law for the formation of [Fe (opt)3 ]2+ was established through spectroscopic measurements at constant and varying pH by isolation method. Order of reaction with respect to each reactant ([U(IV) DCTA] and [Fe (opt)3]3+ was investigated by plotting a graph of ln Aâˆž-At vs time at different temperature ranges. Each reactant was found to follow first order. At pH 3.5 the over all order of reaction was found to be second, having the value of 0.73 M-1 s-1 and rate law is suggested to be ï€¨ï€©ï›ïï€¨ï€©ï›ïï€¨ï€©ï›ï33123opt Fe DCTAH IVUKoptFedtdï€«ï€«ï€«ï€½ . Different thermodynamic functions for the reaction were Ea = 35 ï‚± 0.6 kJ mol-1, ï„H# = 2.4 ï‚± 0.2 kJ mol-1 and ï„S# = -149 ï‚± 3 J mol-1k-1. Activation energy for the reaction was calculated with the help of A rhenius equation. Other activation parameters (Î”Sâ‰ , Î”Hâ‰ ) were determined from the slope and intercept of Eyring equation .At different pH values the rate law was observed as rate = K k1 ï›H+ïn ï›U (IV) DCTAï ï›Fe (opt)3ï+3, where K is equilibrium constant for the protonation reaction ï› U (IV) DCTAï + ï›H+ï = ï›U(IV) DCTA H+ï and k1 is the specific rate constant for the redox reaction ï› U (IV) DCTA H+ï + ï› Fe(opt)3ï+3ï‚® ï› U (V) DCTAï + ï›Fe (opt)3 ï2+.